STRATEGI PEMBELAJARAN PIANO BAGI ANAK DENGAN KARAKTERISTIK BERAGAM DI PENDIDIKAN NON FORMAL - Dhea Elvionita Surya; Anggia Fitri; Nandang Budiman (STKIP Subang, 2025)
This study examines effective music learning strategies for children in the non-formal educational environment of Golden Music, Palangka Raya. The problem in this study is the diverse learning characteristics of children, including children who learn because of parental encouragement, children who have intrinsic motivation, and children with special needs who require an adaptive teaching approach. The purpose of this study is to identify appropriate teaching strategies and methods to support children's musical development, particularly in piano learning. This study uses a descriptive-qualitative method, with observation and interviews with teachers and students as the main data collection techniques. The researcher observed three students with different learning characteristics to understand how learning strategies are applied in practice. The results show that differences in children's motivation, readiness to learn, and concentration significantly affect the effectiveness of the learning process. Overall, these findings highlight that effective music learning in a non-formal environment requires flexible and individually tailored strategies that are adapted to each child's character and needs.